Over the possible role of metal atom clusters in cosmochemistry and in the origin of life - Dioses Castro, Silvio (1992)
We present here the hypothesis of a possible relationship between metal atom clusters and the formation of organic molecules in the interstellar medium and on small bodies as a possible pathway to the origin of such molecules. Two distinct stages are díscussed: a) the possible formation and presence of atom clusters in space and on the primitive Earth, and b) the synthesis of interstellar and terrestrial prebiotic organic molecules, a process in which metal clusters could be the active catalysts. The confirmatíon of these suggestions might be very important in arder to explain the presence of extra-terrestrial organic molecules in the interstellar medium, small bodies and planetary systems, and therefore would have great relevance in cosmochemistry and in the current theories about the origins of life.